Effects of Foliar Applications on Nutrient Concentrations of Kernel, Pomological Properties and Yield of 'Chandler' Walnut Variety at Different Altitudes - Nihal Acarsoy Bilgin (Journal of Agricultural Sciences)
In Turkey, the orchards are being established with the ‘Chandler’ walnut variety in different ecologies, nowadays. Plant nutrition applications are important for optimum yield and quality in terms of growing. In this study conducted at two different altitudes (51 and 740 m) in the orchard, foliar application as urea (5 gr/L), potassium nitrate (10 gr/L), borax (1 gr/L), manganese sulfate (2 gr/L) and zinc sulfate (1.5 gr/L) were sprayed for two years. Following the application, macro and micro nutrient content of kernel and fruit properties were determined. According to this, it was observed that foliar application of boron (B) in terms of nut weight and foliar application of potassium (K) in terms of kernel ratio ranked the first row. The shrinkage ratio, an important quality criterion for walnuts, was found to be low in the high altitude Demirci location (17.43%). However, in the low altitude Saruhanlı location, the shrinkage ratio was reduced with foliar K application. In addition, while all foliar applications had a positive effect on yield, the highest value was measured in Saruhanlı location (3.31 kg tree-1). The macro and micro nutrient content of kernel evaluated, there was an increase in nutrients in the second year, except for K, calcium (Ca) and magnesium (Mg). Phosphorus (0.29 and 0.27%), iron (30.64 and 6.24 ppm), copper (7.64 and 11.35 ppm), zinc (32.42 and 27.03 ppm) and manganese (25.77 and 30.05 ppm) contents of the grain were found to be significant for Demirci and Saruhanlı locations, respectively. Values in Demirci location were higher than Saruhanli location. Additionally, it was also revealed in interaction.